Start-up a novel coupling process with partial nitritation, partial denitrification and anaerobic ammonia oxidation in a single sequencing batch reactor. (February 2022) - Wang, Shaopo; Li, Quan; Zhang, Pengda; Li, Jianyu; Zheng, Jianfeng; Meng, Fansheng; Li, Yajing; Yu, Jingjie
Abstract: A novel process, named single-stage PNDA, that integrates the partial nitritation, partial denitrification and anaerobic ammonia oxidation in a single lab-scale sequencing batch reactor was developed to treat moderate-strength ammonia wastewater (220 mg N/L). Firstly, a single stage partial nitritation-anammox process was started up with the total nitrogen removal efficiencies of approx. 76.22%, and the remaining free ammonia concentration could produce a more sustained inhibition of nitrite oxidizing bacteria(NOB) than low DO condition. Then, the proposed one-stage PNDA process achieved an average total nitrogen removal efficiency of 85.29% by adding sodium acetate in the influent at a concentration of 50 mg COD/L. Microbial community characterization revealed that ammonia-oxidizing bacteria, anammox bacteria, NOB and partial denitrification bacteria coexist in the suspended sludge. The significant enrichment of Thauera and the dominance of Ca. Anammoxoglobus in the Anammox biomass indicate their important role in the improved nitrogen removal performance. This single-stage PNAD process can potentially be applied to further improve the total nitrogen removal efficiency of PN/A process. Graphical abstract: Unlabelled Image Highlights: A concept of PNDA process was proposed in a SBR reactor for ammonia wastewater treatment. In-situ FA exposure is more effective for suppression of NOB than low-DO operation. AnAOB, AOB, PD bacteria and NOB coexisted in floc biomass with enhanced performance.